Transcriptional changes in the xylanolytic filamentous fungus Aspergillus tubingensis NBRC 31125 grown under repressive conditions - Krisnawati, Ririn; Cahyanto, Muhammad Nur; Sardjono, Sardjono; Suroto, Dian Anggraini; Widada, Jaka (Agriculture and Natural Resources, 2023)
Importance of the work: The effect of glucose addition to Aspergillus tubingensis NBRC 31125 grown in xylan medium contributes to understanding the mechanism of carbon catabolite repression related to endoxylanase and β-xylosidase production. Objectives: To investigate and describe changes in endoxylanase production, β-xylosidase production and gene transcription in A. tubingensis NBRC 31125 after glucose addition. Materials & Methods: A. tubingensis NBRC 31125 was grown in xylan medium and xylan medium supplemented with glucose. The crude xylan medium and xylan medium supplemented with glucose were measured for endoxylanase and β-xylosidase production. The RNA of mycelia was extracted and sequenced using the next-generation RNA sequencing Illumina NextSeq 550 platform, followed by different expression genes analysis. Results: Xylan medium supplemented with 5% glucose completely repressed endoxylanase and β-xylosidase production. The more glucose added, the more the production of both enzymes decreased. Transcriptome analysis identified 2,242 downregulated and 2,105 upregulated genes supporting enzyme production. The addition of glucose resulted in the downregulation of 10 genes that were involved in the breakdown of xylan. As activators, the transcription factors XlnR and AraR induced more expression in the xylan medium than in the xylan medium supplemented with glucose. However, repressor CreA and other regulation factors (CreB, CreC and CreD) produced various responses. Main finding: The downregulated genes in the xylan supplemented with glucose medium showed carbon catabolite repression, consistent with glucose regulating endoxylanase and β-xylosidase production in A. tubingensis NBRC 31125.